HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN KEPATUHAN DAN KEMANDIRIAN SANTRI REMAJA - Krisnatuti, Diah; Herawati, Tin; Dini, Nurlaili Rahmah (Jurnal Ilmu Keluarga dan Konsumen, 2011)
The aim of this research was to analyze emotional intelligence, obedience, and autonomy of adolescent santri; correlation between research variables; and difference of some variables based on gender. This research involved 63 adolescent santri who had studied at Boarding School minimum one year. Data was collected by using questionnaires. Data was analyzed by descriptive, Spearman’s correlation, and independent samples t-test. The research results showed that mostly santri had level of obedience in low category. but autonomy and emotional intelligence of adolescent santri in good category. Santri’s emotional intelligence correlated significant with family size (r=0,251, p